Elaboração e validação da versão reduzida do inventário para a avaliação dos transtornos da personalidade – IATP-R - Menezes, Angela Christina Souza (2017)
Personality can be defined as a set of relatively long traits that influence the interactions of the subject with the environment and adaptations to the intrapsychic, physical and social. Thus, only when inflexible and maladaptive do personality traits cause significant functional impairment or subjective suffering, which constitutes Personality Disorder (PD). According to the definition of the Diagnostic and Statistical Manual of Mental Disorders (DSM-5), PDs begin in adolescence or early adulthood, are stable over time and lead to losses and are characterized by the following types: Paranoid; Schizoid; Schizotypal; Antisocial; Borderline; Histrionic; Narcissist; Evitative; Dependent and Obsessive-Compulsive. Recently, with regard to the measurement of PD, the Personality Disorders Assessment Instrument (IATP) was built and validated, which is part of the general evaluation of all the PT groups, but there were no psychometric Consonant with the literature, capable of interpreting the disorder of the Histrionic personality. Therefore, this dissertation had, as a general objective, to obtain evidence of validity of the modified and reduced version of the Inventory for Evaluation of Personality Disorders - IATP-R, including histrionic TP items. The present study had a total sample of 373 participants, of which 343 were university students (non-clinical sample) selected for convenience and 30 patients attended by psychologists and / or psychiatrists who used psychotropic medication, which characterized the clinical sample , Selected using the Simple Random Sampling technique (AAS). The investigation verified the unidimensionality of each set of items in the disorders through analysis. The factorial analysis (PA), using the factorial main axes method (PAF) and direct oblimin rotation, resulted in a final matrix composed by 8 factors that were organized as representative of the following personality disorders: Paranoid; Schizoid; Schizotypal; Narcissist; Evitative; Dependent and Obsessive-Compulsive. For the Anti-Social and Borderline factors, there were no psychometrically satisfactory items and in agreement with the literature capable of interpreting these TPs. The structure indicated a total explained variance of 50.2%, regarding the reliability index, which was calculated through Cronbach's alpha, scored between 0.70 and 0.83, presenting acceptable indexes for this measure. Regarding the TRI analysis, the factors that obtained the best discrimination and difficulty parameters were the TP: Histrionic; Narcissist; Dependent; Paranoid and Schizotypal; All medium to extremely difficult. It should be noted that, in the TRI, seven factors were analyzed, leaving out the schizoid TP factor, because it presented only two items after the FA. The value of the theta (ability) of subjects estimated from the TRI are presented in this investigation as a possible tool for decision making regarding the presence or absence of a specific TP. The results are generally considered satisfactory and the validated instrument can be used as a tool for research purposes in the evaluation of personality disorders.